Pasting of maize and rice starch after high pressure processing: studies based on an acoustic wave sensor - Santos, Mauro D.
tFood is often processed in order to induce modifications intended to improve the product and to give it thedesired characteristics. Among the physical processing methods, high hydrostatic pressure is considereda mild technique with a big potential and it is nowadays used in a variety of products. Gelatinization is stilla not fully understood process and acoustic wave sensors are useful in its study. Therefore, gelatinizationof maize and rice starches processed by high pressure was for the first time studied using such a sensor.Native and pressure processed maize starch were also observed through the microscope and studied bydifferential scanning calorimetry. Besides a significant increase in amylopectin fusion temperature, otherdifferences induced by pressure are visible on the frequency versus temperature plot. Frequency changesrelated to viscosity increase during amylose freeing were significantly reduced on maize starch after highpressure treatment. In spite of some recovery of the system associated with some order regained duringcooling, properties of the starch are far for the initial ones. Gelatinization temperature of rice starchwas higher (77.0◦C) than the one obtained for maize starch (73.5◦C). Other differences were observedbetween rice and maize starches. Namely, final frequency for rice starch after heating/cooling cycle wasnot far from the initial value. Besides, the magnitude of frequency decrease during viscosity increasedue to amylose release was not very different when comparing native rice starch with pressure treatedrice starch. The increase of gelatinization temperature with pressure occurred for both maize and ricestarches. Sensitivity of the sensor allowed to detect differences in gelatinization with small processingtemperature changes in the range from 5◦C to 34◦C.